2011
DOI: 10.1111/j.1399-0012.2011.01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐transplant course and risk of kidney transplant failure in IgA nephropathy patients

Abstract: A rapid pre-transplant course is a strong risk factor for transplant failure in patients with IgAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…It has been suggested that those recipients with a severe and rapidly progressive course in the native kidney have a higher risk of a rIgAN after transplantation, with clinical impact on graft survival. A rapid loss of renal function, defined as DGFR > 30 mL/min/1.73 m 2 per year, between diagnosis of IgAN and initiation of RRT was a strong predictor of graft loss after kidney transplantation [6]. These previous observations are in agreement with the finding of an exponentially decreasing relation between age at transplantation and risk of rIgAN reported in this study.…”
Section: Pretransplant Serum Gd-iga1 Levelssupporting
confidence: 92%
“…It has been suggested that those recipients with a severe and rapidly progressive course in the native kidney have a higher risk of a rIgAN after transplantation, with clinical impact on graft survival. A rapid loss of renal function, defined as DGFR > 30 mL/min/1.73 m 2 per year, between diagnosis of IgAN and initiation of RRT was a strong predictor of graft loss after kidney transplantation [6]. These previous observations are in agreement with the finding of an exponentially decreasing relation between age at transplantation and risk of rIgAN reported in this study.…”
Section: Pretransplant Serum Gd-iga1 Levelssupporting
confidence: 92%
“…Annualized loss of eGFR may have been a more meaningful measure of pre-transplant disease activity 20 , however creatinine at time of biopsy was not consistently documented. Post-transplantation data included allograft type (living vs. deceased donor), induction and maintenance immunosuppression, biopsy proven allograft rejection and grade, BK viremia and/or nephropathy, occurrence of proteinuria, nephrotic syndrome (defined as proteinuria > 3.5g per gram of creatinine, hypoalbuminemia, and clinical documentation), hypertension (defined as BP > 140/90 mmHg or need for antihypertensives to achieve a BP of < 140/90mmHg), graft loss (defined as return to dialysis or re-transplantation) and mortality.…”
Section: Methodsmentioning
confidence: 97%
“…Recurrence in the allograft is more common in children than in adults 79 and is associated with crescentic disease and a rapid decline in renal function before engraftment. 81 In most transplantation centers, recurrent disease is not more frequent in kidneys from living related donors than in those from deceased donors, although the possibility of familial disease or covert IgA nephropathy mandates careful evaluation before nephrectomy. Whether the circulating level of galactose-deficient IgA1 or anti-glycan antibodies influences the post-transplantation course remains unknown.…”
Section: Pathological Prognostic Markersmentioning
confidence: 99%